Online Marketing Supports Promotion And Advertising Sales In Communities Dolly Localization - Wiwik Handayani; Sri Muljaningsih; Helmina Ardyanfitri (LPPM of NAROTAMA UNIVERSITY, 2018)
Dolly Society still does not yet have online marketing knowledge, which can help market products that have been produced. Online marketing is one way to market SMEs to increase sales. Nowadays technology is progressing so that almost every marketing activity can be helped by using the internet. Promotions and advertising activities can also be done online so that they are more efficient. In the past, buying must meet the seller, so now you don't have to meet the seller. Can be admitted at home like the sale of other online products. For this reason, in community service, it provides broader and more varied marketing knowledge. Online marketing training was attended by mothers who had previously received training in making catfish-based products. So that after being able to make it can also sell.